Pengaruh Tingkat Kurs Rupiah, Harga Emas dan Harga Minyak terhadap Indeks LQ 45 Periode Maret 2013 – Juni 2016 - Muhammad Ikhwan Nugraha (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2020)
This research aimed to analyze the effects of some macroeconomic variables for the movement of LQ 45 Index. Those macroeconomic variables used among other things were rupiah exchange rate, gold price and oil price.The population of this research was LQ 45 Index in Indonesia Stock Exchange (BEI) from March 2013 to June 2016 and the independent variables in the same time period. The total samples, the same as the population, were 40 monthly data which were determined through a census method. The data were obtained from Indonesian Stock Exchange and other reputable websites. The data analysis was performed with the classical assumption and hypothesis testing by multiple regression.The results of this study showed that rupiah exchange rate and oil price had a significant effect towards LQ 45 Index, while gold price did not have a signifiant effect towards LQ 45 Index.